Disabled church, disabled society : the implications of autism for philosophy, theology and politics - Gillibrand, John, 1960- (Jessica Kingsley Publishers, 2010)
'Combining poignant personal honesty with an extraordinarily wide range of theological and philosophical learning, John Gillibrand has written a book that takes us well beyond the usual boundaries of studies in autism to raise questions about our human identity, suggesting that we jeopardize human dignity most when we try to bind it to the characteristics we can recognize and value and understand as mirroring only our own faces.'. - from the Foreword by Dr Rowan Williams, Archbishop of Canterbury. In this moving and intelligent book John Gillibrand, an Anglican priest, draws on his experience.